2021
DOI: 10.5755/j01.sace.29.2.28497
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategies for Healing Internal Environments and Workplaces. A Theoretical Framework

Abstract: The purpose of this paper is to construct a theoretical framework for designing healing environments by drawing from existing research. The approach of the paper surveys the literature on how elements of the design have been brought to bear on healing. This effort leads to a holistic approach that considers multiple dimensions of healing as both an individual and social process. The findings of the paper are harnesses that knowledge to provide a theoretical framework based on three design strategies: 1) suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Rate the highest agreement on clear functions distribution in the building (V9) is for building (5) with a value of (3.77), while the lowest value is for building (3) with a value of (2.55). Values higher agreement on the presence of attention to communication between the internal corridors and the external spaces(V10) is for building (4) with a value of (3.73), while the lowest value is for building (3) with a value of (2.50).…”
Section: Discuss the Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Rate the highest agreement on clear functions distribution in the building (V9) is for building (5) with a value of (3.77), while the lowest value is for building (3) with a value of (2.55). Values higher agreement on the presence of attention to communication between the internal corridors and the external spaces(V10) is for building (4) with a value of (3.73), while the lowest value is for building (3) with a value of (2.50).…”
Section: Discuss the Resultsmentioning
confidence: 95%
“…The results of the questionnaire of the selected sample of the study cases (5) indicated that there is a significant discrepancy in the responses to the study cases, according to Table 4 by adopting the five-point Likert scale as follows:…”
Section: Discuss the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The definition of the World Health Organization emphasizes decreasing the importance of the idea that health includes the absence of pathological symptoms only and the importance of adopting preventive and curative measures accompanying the usual conditions of the individual. Healing design as a strategy of the design process could be achieved or based on three design strategies: 1) supporting strategies that use specific elements to reinforce physical health, vital life energy, and psychological well-being; 2) balancing strategies that are oriented toward harmonizing those elements; and 3) nourishing strategies that address emotions, spiritual life, and the soul (Younis, 2021).…”
Section: Concept Of Healthmentioning
confidence: 99%